2014
DOI: 10.14814/phy2.12187
|View full text |Cite
|
Sign up to set email alerts
|

Subsarcolemmal lipid droplet responses to a combined endurance and strength exercise intervention

Abstract: Muscle lipid stores and insulin sensitivity have a recognized association although the mechanism remains unclear. We investigated how a 12‐week supervised combined endurance and strength exercise intervention influenced muscle lipid stores in sedentary overweight dysglycemic subjects and normal weight control subjects (n = 18). Muscle lipid stores were measured by magnetic resonance spectroscopy (MRS), electron microscopy (EM) point counting, and direct EM lipid droplet measurements of subsarcolemmal (SS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 100 publications
3
48
1
Order By: Relevance
“…6 and 7). The latter finding is in line with recent results (3,28,35) and together with a concomitant improved insulin sensitivity in the present study (see Ref. 6) emphasizes a role of subsarcolemmal LDs in insulinmediated glucose uptake.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…6 and 7). The latter finding is in line with recent results (3,28,35) and together with a concomitant improved insulin sensitivity in the present study (see Ref. 6) emphasizes a role of subsarcolemmal LDs in insulinmediated glucose uptake.…”
Section: Discussionsupporting
confidence: 94%
“…LDs are distributed in between the myofibrils (intermyofibrillar LDs) and just beneath the surface membrane (subsarcolemmal LDs). Several studies have suggested that only the subsarcolemmal LDs are associated with insulin resistance in humans (3,9,28,35). However, a causal relationship has been questioned by the lack of association after aerobic training (35) and by the fact that white rat muscles (type 2 fibers) were devoid of subsarcolemmal LDs despite being insulin resistant (24).…”
mentioning
confidence: 99%
“…Body composition was measured by magnetic resonance imaging (MRI)/MR spectrometry (MRS) (Li et al . ). Plasma concentration of mature myostatin protein (free or latent) was measured with an ELISA kit (Cat# DGDF80, R&D Systems), according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 97%
“…All base positions were of high quality (Phred score >30). Alignment of sequenced cDNA reads to the RefSeqGene database as transcriptome reference and quantitative analysis of the transcripts was done as described by Li et al (2014) 37 .…”
Section: Methodsmentioning
confidence: 99%